Evaluation of the Effect of Contraceptives on Prevalence of Candida Species on Vaginal Candidiasis in Dhaka, Bangladesh (Bangladesh Journal of Medical Microbiology, 2016)
This study was designed to find out the relationship between uses of different contraceptives and the prevalence of vaginal candidiasis. High vaginal swabs were obtained from 350 women in the age group of 15-45 years with vaginal discharge attending at Sir Salimullah Medical College Hospital, Dhaka, which comprised of 247 contraceptive users & 103 non-contraceptive users. A detailed clinical history and a thorough examination of all the cases were done. After making the clinical diagnosis, appropriate tests for diagnosing Candidiasis were done by using standard procedures. Of the 247 women of contraceptive users, Candida species was isolated in 140 (56.7%) cases compared to 32 (31.1%) from 103 non-contraceptive users (p value